Hubungan Kepemimpinan dan Motivasi terhadap Kinerja Karyawan pada Perusahaan Socolatte di Kecamatan Bandar Baru Kabupaten Pidie Jaya - Lena Susianti; Ahmad Baihaqi; Romano Romano (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
Abstract. Socolatte is a cocoa bean processing industry into various chocolate preparations. In running a business, of course, the role of the leadership is needed, in this case the owner of the company and the role of the employees as the driving force of the company. Employees as business actors need to be regulated in such a way that the goals or objectives of the company can be achieved. The presence of a leader is needed to direct and supervise the work of employees so that the goals of the company can be achieved optimally. In addition, the motivation (motivation from within) the employee concerned is also very necessary at work. The combination of the leadership role and employee motivation will determine the performance of the employee. This study aims to determine whether there is a relationship between top management or company owners on employee performance, and whether there is a relationship between work motivation and employee performance at the Socolatte company, as well as the close relationship between variables. The sample selection was carried out using the census method with a total of 33 employees. The data used are primary and secondary data. The analytical method used is the Chi Square method and the instrument test uses validity and reliability tests. The results showed that the p value in the Chi Square test for the first hypothesis regarding the relationship between. leadership and employee performance was 0.167. This number is greater than the value of = 0.05. Based on the decision-making criteria for the chi-square statistical test where if p α, then the decision is to accept H0, which means that the relationship between leadership variables and employee performance at Socolatte company is not significant. Then the p value in the Chi Square test for the second hypothesis regarding the relationship between work motivation and employee performance is 0.022. This number is smaller than the value of = 0.05. Based on the decision- making criteria for the chi square statistical test where if p α, then the decision is to reject H0, which means that the relationship between work motivation and employee performance is significant. Then for the close relationship between motivational variables and performance, it is obtained from the contingency coefficient value of 0.370 or in the range of 0.20 - 0.40. This means that the two variables have a small (not close) relationship. However, this relationship cannot be ignored because if there is a change in the value of a work motivation variable, it will still make a change even though it is a small part of the performance variable.